2003
DOI: 10.1159/000069863
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Antigen Targeting by a Humanised Monoclonal Antibody: An Early Phase II Trial of Sibrotuzumab in Patients with Metastatic Colorectal Cancer

Abstract: Background: A novel immunological approach to colon cancer therapy is the antibody targeting of the fibroblast activation protein (FAP), which is highly expressed by stroma cells of this tumour. Unconjugated sibrotuzumab (BIBH 1), which is a humanised version of the murine anti-FAP mAb F19, was investigated for its anti-tumour activity, safety and pharmacokinetics. Patients and Methods: Patients with metastatic colorectal cancer received weekly intravenous infusions of unconjugated sibrotuzumab at a dose of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
223
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(223 citation statements)
references
References 11 publications
0
223
0
Order By: Relevance
“…In antibody-based imaging studies, anti-FAP antibodies exhibited highly specific tumor targeting in patients (40). However, although a humanized anti-FAP antibody (mAb F19; sibrotuzumab) was well tolerated, it showed no efficacy in a phase II trial for metastatic colorectal cancer (39,53). It is important to note, however, that this particular antibody does not inhibit FAP activity or have direct cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In antibody-based imaging studies, anti-FAP antibodies exhibited highly specific tumor targeting in patients (40). However, although a humanized anti-FAP antibody (mAb F19; sibrotuzumab) was well tolerated, it showed no efficacy in a phase II trial for metastatic colorectal cancer (39,53). It is important to note, however, that this particular antibody does not inhibit FAP activity or have direct cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…A humanized version of mAb F19 (sibrotuzumab), a first generation anti-FAP antibody, however, failed to show measurable therapeutic activity (24) in phase I/II clinical trials despite excellent tumor stroma targeting properties (25). In addition, 8 of 26 sibrotuzumab-treated patients developed human-anti-human antibodies (HAHA) with a change in pharmacokinetics and reduced tumor uptake in 4 of them.…”
Section: Introductionmentioning
confidence: 99%
“…10 Given its ubiquitous expression in both primary and metastatic colorectal carcinomas, FAP has been targeted by monoclonal antibodies, 11 but these non-inhibitory antibodies did not show clinical activity. [11][12][13] We have previously shown that forced FAP overexpression by tumor cells in an animal model results in a significant enhancement in tumor growth. 14 This tumor growth potentiation is thought to be due to its proteolytic activity, as mutation of the catalytic serine residue abolishes FAP's proteolytic activity and subsequently eliminates the tumor growth advantage.…”
Section: Introductionmentioning
confidence: 99%